IDNLearn.com: Where questions are met with accurate and insightful answers. Join our interactive community and get comprehensive, reliable answers to all your questions.
Sagot :
Answer:
[tex](X+10)^2 = 106[/tex]
Step-by-step explanation:
To convert the quadratic equation [tex]X^2+20x-6=0[/tex] into the form [tex](x-p)^2=q[/tex], we need to complete the square. Let's go through this step-by-step:
First, let's start with our equation:
[tex]X^2+20x-6=0[/tex]
Move the constant term to the right side of the equation:
[tex]X^2+20x = 6[/tex]
To complete the square, we take half of the coefficient of x, square it, and add and subtract it from both sides:
Half of 20 is 10, and [tex]10^2 = 100[/tex]
[tex]X^2+20x+100 = 6+100[/tex]
Simplify the right side:
[tex]X^2+20x+100 = 106[/tex]
The left side is now a perfect square trinomial:
[tex](X+10)^2 = 106[/tex]
This is almost in[tex](x-p)^2=q[/tex] form. We just need to adjust it slightly:
[tex](X-(-10))^2 = 106[/tex]
Therefore, in [tex](x-p)^2=q[/tex] form, the equation [tex]X^2+20x-6=0[/tex] becomes:
[tex](X+10)^2 = 106[/tex]
Where [tex]p = -10[/tex] and [tex]q = 106[/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.